2012
DOI: 10.3201/eid1806.111421
|View full text |Cite
|
Sign up to set email alerts
|

Local Transmission of Imported Endemic Syphilis, Canada, 2011

Abstract: Endemic (nonvenereal) syphilis is relatively common in nonindustrialized regions of the world. We describe a case of local transmission in Canada and review tools available for confirming a diagnosis. Improved molecular tools and global clinical awareness are needed to recognize cases of endemic syphilis imported to areas where it is not normally seen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 8 publications
0
25
0
Order By: Relevance
“…Imported cases of yaws and bejel have been documented in children in Europe and the United States [30]–[32], and a case of local transmission of bejel was reported in 2012 in Canada among a family who had lived in a refugee camp in the Republic of Senegal and whose children were all infected [33]. Diagnosis of imported cases is hampered by the limited knowledge and lack of awareness among health care workers in western countries, who may need to include them in the differential diagnosis.…”
Section: Epidemiological and Geographical Differencesmentioning
confidence: 99%
“…Imported cases of yaws and bejel have been documented in children in Europe and the United States [30]–[32], and a case of local transmission of bejel was reported in 2012 in Canada among a family who had lived in a refugee camp in the Republic of Senegal and whose children were all infected [33]. Diagnosis of imported cases is hampered by the limited knowledge and lack of awareness among health care workers in western countries, who may need to include them in the differential diagnosis.…”
Section: Epidemiological and Geographical Differencesmentioning
confidence: 99%
“…Although several minor genetic differences have been identified among the subspecies, the means to distinguish between these species remain limited (2,3). It is noteworthy, however, that a recent case report from Canada described the use of genomic techniques to demonstrate transmission of endemic syphilis in Canada (4). …”
Section: Treponema Pallidum and Related Agentsmentioning
confidence: 99%
“…A nice example of the clinical use of molecular tools to diagnose an imported case of endemic syphilis in Canada is represented by the recent work of Fanella et al They first targeted bmp, polA, and TP0574 by PCR to detect treponemal DNA in a sample harvested from a patient's oral lesion and subsequently used both arp sequencing and the tprC/tprI RFLP assays to identify the etiological agent as T. pallidum subsp. endemicum (221).…”
Section: Direct Detection Methodsmentioning
confidence: 99%
“…The primary stage of the disease was thought to have occurred in Mali, where the patient had lived before moving to France a few months earlier. Recently, Fanella et al reported a case of endemic syphilis in Winnipeg in a 1-year-old patient born to a couple who had lived in a refugee camp in Senegal for 20 years before immigrating to Canada (221). Further assessment of all family members (parents and eight siblings) revealed that all of the couple's children were affected.…”
Section: Imported Cases Of Endemic Treponematosesmentioning
confidence: 99%